Synoptic and Seasonal Variations of the Ice-Ocean Circulation in the Arctic: A Numerical Study - Warn-Varnas, Alex; Allard, Richard; Piacsek, Steve (1991)
The circulations of the Arctic ice cover and ocean are investigated using a coupled ice-ocean model. The coupling is strong and two-way for synoptic time scales, but is limited on seasonal time scales: the geostrophic ocean currents are not changed by the computed heat and salt fluxes. The ice-drift motion, Ekman transports and the wind-driven part of the barotropic circulation are examined for the months of February and August 1986, representing different atmospheric forcing, ice thickness and ice-strength regimes. Initial examination of the results revealed no significant seasonal dependence of ice-drift response on the synoptic time scale, other than larger velocities with larger wind stresses. Daily maximum ice-drift velocities range from 20-40 cm/s in February, and 15-30 cm/s in August. The corresponding mean monthly maximum drifts were 11 and 9 cm, respectively. The drag associated with the geostrophic currents plays a much bigger role in the summer because of the lighter atmospheric stresses. The well-known reversal of the normally clockwise Beaufort Gyre to a cyclonic system in August takes place in a few days and lasts well into September. In February, the Beaufort Gyre varies between a large, clockwise system covering all the Canadian Basin to a small, tight gyre centered over the southern Beaufort Sea, without any hint of reversal or disappearance. Large areas of strong divergence were found in the Ekman transport patterns, as well as the ice-divergence fields, indicating areas where ice thinning, openings and new ice formation might occur. In August this occurred in the Chukchi Sea, and in February just north of Novaya Zemlya. Pub. in Annals of Glaciology, v15 p54-62, 1991.